If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + 4 = 4h + 11 Reorder the terms: 4 + 5h = 4h + 11 Reorder the terms: 4 + 5h = 11 + 4h Solving 4 + 5h = 11 + 4h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4h' to each side of the equation. 4 + 5h + -4h = 11 + 4h + -4h Combine like terms: 5h + -4h = 1h 4 + 1h = 11 + 4h + -4h Combine like terms: 4h + -4h = 0 4 + 1h = 11 + 0 4 + 1h = 11 Add '-4' to each side of the equation. 4 + -4 + 1h = 11 + -4 Combine like terms: 4 + -4 = 0 0 + 1h = 11 + -4 1h = 11 + -4 Combine like terms: 11 + -4 = 7 1h = 7 Divide each side by '1'. h = 7 Simplifying h = 7
| w(20w-73)=-63 | | 6(x^2+x-20)=0 | | 5n+43=-2(1-7n) | | 6y-8=4y+2 | | 7+7x=7+8x | | x+5x+4x-6=180 | | 7=4y-2y+1 | | 3v-5=16 | | z^2-30z+c=0 | | (13b-7)-3(4b+3)=-6 | | 4x-5=(x-1) | | 3.5(x-2)=12-.5x | | -63+8x=173x | | 4x^3-80x^2+400x=500 | | -9x-155=85+3x | | 5x-3=-x+3 | | 10+3x=-5x+98 | | 5b+3=4b-2 | | 6x-4=-4-2x | | 3x+9=2y-4 | | 6m^2+15m+3=0 | | -2x+5=10+4x | | 2x+4=-x-20 | | 22=2y | | 0=x^2+26x+232 | | x+1+2x+2+3x+3+4x=56 | | 2x+7=-x-1 | | 11x-79=47+5x | | 5x-3+2x=2x+2 | | 8=2*b^2 | | (x*x)-5=23 | | 8=2xb^2 |